Mechanism of Internet of Things (IoT) Integrated with Radio Frequency Identification (RFID) Technology for Healthcare System. (22nd March 2022) - Mohammad, Gouse Baig; Shitharth, Shitharth; Syed, Salman Ali; Dugyala, Raman; Rao, K.Sreenivasa; Alenezi, Fayadh; Althubiti, Sara A; Polat, Kemal
Abstract : Radio frequency identification (RFID) technology has already demonstrated its use. RFID is used in many productions for different applications, for example, apparatus chasing, personal and vehicle access panels, logistics, baggage, and safety items in departmental stores. The main benefits of RFID are optimizing resources, quality customer service, improved accuracy, and efficient business and healthcare procedures. In addition, RFID can help to recognize appropriate information and help advance the probability of objects for certain functions. Nevertheless, RFID components need to be studied for use in healthcare. Antennas, tags, and readers are the main components of RFID. The study of these elements provides an understanding of the usage and integration of these components in healthcare environments. The security of the patient is now a global alarm for public health, particularly among older people who need integrated and technologically integrated physiological health monitoring systems to monitor medical needs and manage them. This paper proposes using Internet of Things (IoT) and RFID tags as an effective healthcare monitoring system. In this method, we utilize RFID dual-band protocols that are useful for identifying individual persons and are used to monitor body information using high frequency. The patient's physiological data are monitored and collected by sensors to recognize the patient, using an RFID tag. The IoT-based RFID healthcare provides the elderly and people with physiological information. The aim is also to secure patient health records using the signing algorithm based on the hyperelliptic curve (HEC) and to provide the physician with access to health information for patients. Furthermore, the confidentiality of the medical records for patients of variable length is provided. The evaluation reveals the algorithm proposed for optimum health care with different genus curves.